Evaluation of integrated disease surveillance and response (IDSR) core and support functions after the revitalisation of IDSR in Uganda from 2012 to 2016 - Masiira, Ben (BMC Public Health, 2019)
BACKGROUND: Uganda is a low income country that continues to experience disease outbreaks caused by emerging and re-emerging diseases such as cholera, meningococcal meningitis, typhoid and viral haemorrhagic fevers. The Integrated Disease Surveillance and Response (IDSR) strategy was adopted by WHO-AFRO in 1998 as a comprehensive strategy to improve disease surveillance and response in WHO Member States in Africa and was adopted in Uganda in 2000. To address persistent inconsistencies and inadequacies in the core and support functions of IDSR, Uganda initiated an IDSR revitalisation programme in 2012. The objective of this evaluation was to assess IDSR core and support functions after implementation of the revitalised IDSR programme. METHODS: The evaluation was a cross-sectional survey that employed mixed quantitative and qualitative methods. We assessed IDSR performance indicators, knowledge acquisition, knowledge retention and level of confidence in performing IDSR tasks among health workers who underwent IDSR training. Qualitative data was collected to guide the interpretation of quantitative findings and to establish a range of views related to IDSR implementation. RESULTS: Between 2012 and 2016, there was an improvement in completeness of monthly reporting (69 to 100%) and weekly reporting (56 to 78%) and an improvement in timeliness of monthly reporting (59 to 93%) and weekly reporting (40 to 68%) at the national level. The annualised non-polio AFP rate increased from 2.8 in 2012 to 3.7 cases per 100,000 population < 15 years in 2016. The case fatality rate for cholera decreased from 3.2% in 2012 to 2.1% in 2016. All districts received IDSR feedback from the national level. Key IDSR programme challenges included inadequate numbers of trained staff, inadequate funding, irregular supervision and high turnover of trained staff. Recommendations to improve IDSR performance included: improving funding, incorporating IDSR training into pre-service curricula for health workers and strengthening support supervision. CONCLUSION: The revitalised IDSR programme in Uganda was associated with improvements in performance. However in 2016, the programme still faced significant challenges and some performance indicators were still below the target. It is important that the documented gains are consolidated and challenges are continuously identified and addressed as they emerge.